Comparative Genomics of Closely Related Tetragenococcus halophilus Strains Elucidate the Diversity and Microevolution of CRISPR Elements - Matsutani, Minenosuke; Wakinaka, Takura; Watanabe, Jun; Tokuoka, Masafumi; Ohnishi, Akihiro (Frontiers in Microbiology, 2021)
Tetragenococcus halophilus—a halophilic lactic acid bacterium—is frequently used as a starter culture for manufacturing fermented foods. Tetragenococcus is sometimes infected with bacteriophages during fermentation for soy sauce production; however, bacteriophage infection in starter bacteria is one of the major causes of fermentation failure. Here, we obtained whole-genome sequences of the four T. halophilus strains YA5, YA163, YG2, and WJ7 and compared them with 18 previously reported genomes. We elucidated five types of clustered regularly interspaced short palindromic repeat (CRISPR) loci in seven genomes using comparative genomics with a particular focus on CRISPR elements. CRISPR1 was conserved in the four closely related strains 11, YA5, YA163, and YG2, and the spacer sequences were partially retained in each strain, suggesting that partial deletions and accumulation of spacer sequences had occurred independently after divergence of each strain. The host range for typical bacteriophages is narrow and strain-specific; thus these accumulation/deletion events may be responsible for differences in resistance to bacteriophages between bacterial strains. Three CRISPR elements, CRISPR1 in strains 11, YA5, YA163, and YG2, CRISPR2 in strain WJ7, and CRISPR2 in strain MJ4, were inserted in almost the same genomic regions, indicating that several independent insertions had occurred in this region. As these elements belong to class 1 type I-C CRISPR group, the results suggested that this site is a hotspot for class 1, type I-C CRISPR loci insertion. Thus, T. halophilus genomes may have acquired strain-specific bacteriophage-resistance through repeated insertion of CRISPR loci and accumulation/deletion events of their spacer sequences.